Inhibitory effects of Phyllanthus emblica L. on hepatic steatosis and liver fibrosis in vitro. (January 2016) - Lu, Chi-Cheng; Yang, Shu-Han; Hsia, Shih-Min; Wu, Chi-Hao; Yen, Gow-Chin
Highlights: Phyllanthus emblica L. possesses several biological properties. Ellagic acid is enriched in the water extract of P. emblica L. fruits (WEPL). WEPL inhibits cellular steatosis in the established steatotic HepG2 cells. Reduction of liver fibrosis in hepatic stellate cells (HSCs) by WEPL. WEPL has a potential effect on improving NAFLD. Graphical Abstract: Abstract: Phyllanthus emblica L. exerts multiple biological functions, and its fruit possesses hepatoprotective benefits. However, the underlying mechanisms of these activities remain unclear. This study aimed to investigate the potential impact of P. emblica on improving nonalcoholic fatty liver disease (NAFLD). Free fatty acid mixture-induced HepG2 cells and leptin-induced HSC-T6 hepatic stellate cells were used to mimic nonalcoholic steatohepatitis and hepatic fibrosis, respectively. Ellagic acid (EA) was identified as a major compound in the water extract of P. emblica fruits (WEPL). WEPL significantly decreased fat accumulation and ROS production by altering lipogenesis-related gene expression and stimulating AMP-activated protein kinase (AMPK) signalling in treated HepG2 cells. WEPL also inhibited hepatic fibrosis in HSC-T6 cells and induced mitochondrial apoptosis. Importantly, EA was shown to inhibit cellular steatosis and liver fibrosis in vitro . In conclusion, WEPL reduces lipogenesis in hepatocytes and fibrotic cells, suggesting that WEPL has the potential to improve NAFLD.